Antifungal Effect of Allium tuberosum, Cinnamomum cassia, and Pogostemon cablin Essential Oils and Their Components Against Population of Aspergillus Species. Issue 5 (6th May 2013) - Kocevski, Dragana; Du, Muying; Kan, Jianquan; Jing, Chengjun; Lačanin, Ines; Pavlović, Hrvoje
Abstract: Antifungal activity of Allium tuberosum (AT), Cinnamomum cassia (CC), and Pogostemon cablin (Patchouli, P) essential oils against Aspergillus flavus strains 3.2758 and 3.4408 and Aspergillus oryzae was tested at 2 water activity levels ( a w : 0.95 and 0.98). Main components of tested essential oils were: allyl trisulfide 40.05% (AT), cinnamaldehyde 87.23% (CC), and patchouli alcohol 44.52% (P). The minimal inhibitory concentration of the plant essential oils against A. flavus strains 3.2758 and 3.4408 and A. oryzae was 250 ppm ( A. tuberosum and C. cassia ), whereas Patchouli essential oil inhibited fungi at concentration > 1500 ppm. The essential oils exhibited suppression effect on colony growth at all concentrations (100, 175, and 250 ppm for A. tuberosum ; 25, 50, and 75 for C. cassia ; 100, 250, and 500 for P. cablin essential oil). Results of the study represent a solution for possible application of essential oil of C. cassia in different food systems due to its strong inhibitory effect against tested Aspergillus species. In real food system (table grapes), C. cassia essential oil exhibited stronger antifungal activity compared to cinnamaldehyde.